Pendidikan Karakter Berbasis Nilai - Otaya, Lian G. (Nadwa, 2014)
Internalization of values-based character education on student himself can be done through an objective and transparent assessment system. This will be useful to foster honesty, discipline, and responsibility of students. Objective assessment was actually born of conscience. The real truth in it as something that is produced by conscience is something that is pure and candid. Transparent assessment of the implementation of the assessment should be known, from the aspect of the values obtained, the basic decision-making, processing until the final result indicated value, and acceptable. With such a rating system that would give birth to a student who has a character to help form a strong mental. Strong mental is precondition to be qualified competitive human.